Viking Camps Case Studies and Comparisons - Hedenstierna-Jonson, Charlotte; Irene, García-Garrido (Taylor & Francis, 2023)
Archaeology, Medieval Iberia, Viking, Viking Camps, Viking history, Viking settlement